2012
DOI: 10.1525/mp.2012.30.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Mental Practice in Music Memorization: An Ecological-Empirical Study

Abstract: 1 n.bernardi2@campus.unimib.it, 2 alexschories@gmx.de, 3 jabusch@hfmdd.de, 4 barbara.colombo@unicatt.it, 5 altenmueller@hmt-hannover.de ABSTRACTMental Practice (MP) refers to a complex network of strategies for improving musical performance without physically performing at the instrument. The present study represents an attempt to describe cross-individual differences in the use of different MP strategies, allowing direct predictions on which strategies are more likely to be effective. Sixteen pianists were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 33 publications
(32 reference statements)
4
55
2
3
Order By: Relevance
“…Imagery brought about improvements in aspects of music performance, such as movement velocity and movement timing. However, consistent with music imagery research (e.g., Bernardi, Schories et al, 2013;Ross, 1985), improvements brought about by imagery were smaller than those that occurred as a result of physical practice. Further examination of the different imagery practice strategies used by participants in the mental practice group revealed differences in the extent to which motor imagery and auditory imagery improved aspects of performance.…”
Section: Imagery As a Performance Enhancement Technique For Musicianssupporting
confidence: 74%
“…Imagery brought about improvements in aspects of music performance, such as movement velocity and movement timing. However, consistent with music imagery research (e.g., Bernardi, Schories et al, 2013;Ross, 1985), improvements brought about by imagery were smaller than those that occurred as a result of physical practice. Further examination of the different imagery practice strategies used by participants in the mental practice group revealed differences in the extent to which motor imagery and auditory imagery improved aspects of performance.…”
Section: Imagery As a Performance Enhancement Technique For Musicianssupporting
confidence: 74%
“…In contrast, the subjects in the PP group received the following instructions: “ You have 7 min to practice this piece and then you will perform it again. You can freely use whatever practice method you prefer, as long as it includes physically playing the instrument .” The PP subjects were not asked to avoid or limit their mental operations during practice, as these constrains have been proven to be confounding and relatively ineffective (Bernardi et al, 2013). This choice designated our PP condition as the “natural,” ecologic practice condition and the one with which the subjects were more familiar.…”
Section: Methodsmentioning
confidence: 99%
“…Extended research in the field of sport psychology has shown that MP improves actual motor performance, although not to the same extent as physical practice (PP; Feltz and Landers, 1983). In both sport and music performance it has been evidenced that proper combinations of MP and PP yield results similar to extended PP alone (Kopiez, 1990; Theiler and Lippman, 1995; Bernardi et al, 2013). More recently, studies have been designed to understand the mechanisms that are responsible for these outcomes (Munzert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that there is a positive association between the musician's auditory imagery abilities and success at learning novel piano pieces from notation in the absence of auditory feedback (Highben and Palmer, 2004). Use of auditory imagery during mental practice is associated with better post-practice performance (Bernardi et al, 2013). …”
Section: Interaction Of Multisensory and Motor Images In Musical Imagerymentioning
confidence: 99%